1982
DOI: 10.1111/j.1440-6055.1982.tb01763.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SUBGENUS AUSTRALOPHLEBOTOMUS THEODOR OF PHLEBOTOMUS RONDANI AND BERTÉ (DIPTERA: PSYCHODIDAE)

Abstract: A key is given to the 8 recorded species of Australophlebotomus (6 from Australia, 2 from Papua New Guinea). Both sexes of 3 species are known. The taxonomy of 6 species is brought up to date, 2 new ones (Phlebotomus acuminatus and P. mackerrasi) are described, a taxonomic problem involving the 2 common Australian species is resolved and the known distribution of species is shown. The affinities, status, diagnosis, origin, food preferences and trophic morphology of Ausiralophlebotomus are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…This communication reports the southermost record of a Phlebotominae in the World, being the previous records Australophlebotomus brevifilis (Tonnoir, 1935) and A. brevifiloides Fairchild, 1952 from mainland Victoria, Australia (Lewis & Dyce 1982). On the other hand, the northern limit of the distribution area of Phlebotominae is represented by L. vexator (Coquillett, 1907) from Perth, Ontario, Canada (Downes 1972) up to 44ºN.…”
supporting
confidence: 56%
“…This communication reports the southermost record of a Phlebotominae in the World, being the previous records Australophlebotomus brevifilis (Tonnoir, 1935) and A. brevifiloides Fairchild, 1952 from mainland Victoria, Australia (Lewis & Dyce 1982). On the other hand, the northern limit of the distribution area of Phlebotominae is represented by L. vexator (Coquillett, 1907) from Perth, Ontario, Canada (Downes 1972) up to 44ºN.…”
supporting
confidence: 56%
“…Fourth, the hypothesis requires that Leishmania adapted to murid rodents separately in the Neotropical, the Nearctic and the Palaearctic. Fifth, fossil evidence indicates that phlebotomine sand flies (Lewis 1982), the only vectors, and murid rodents (Nowak 1991), the most important zoonotic reservoirs, both originated in the Palaearctic, making it improbable that Leishmania originated in the Neotropical. Noyes (1998) himself acknowledged that his hypothesis of a Neotropical origin of Leishmania is inconsistent with the position of Sauroleishmania external to Leishmania (Lainson & Shaw 1987) or the classification of New and Old World species of phlebotomine sand flies in separate genera (Williams 1993).…”
mentioning
confidence: 99%
“…There were fewer electrophoretic differences with the NW genus Lutzomyia (Jaccard 0.81, Table III below diagonal) and related subgenera (0.81-0.82) than with Phlebotomus (0.85) or Spelaeophlebotomus (0.94). Remarkably, there was a very low metric distance with the genus Warileya (Mahalanobis 293, Table III above diagonal), which parallels the observation of primitive characters, as those described for Warileya, in some Australophlebotomus species , Lewis & Dyce 1982. The relatively lower divergence between Australophlebotomus and South American taxa could be attributed to either convergence or common ancestry.…”
Section: Discussionmentioning
confidence: 69%
“…It was classified by Lewis and Dyce (1982) as a subgenus of Phlebotomus, but our study indicated relatively more affinities of Australophlebotomus with South American than with Afrotropical species (Fig. 1).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation